Right Ventricular STEMI - A Case Simulation - Forrest Hill (Association of American Medical Colleges, 2011)
Abstract This resource is a simulation case utilizing a simulation manikin. In the case, a medical student or first-year resident cares for a patient presenting with chest pain diagnosed as a right-sided ventricular ST-elevation myocardial infarction (STEMI). The case takes students from presentation to disposition while walking through many common pitfalls of managing a right ventricular STEMI. Use of a manikin simulation immerses the student in the scenario of a patient presenting with chest pain. The student reinforces and augments his or her knowledge by working through the diagnosis and treatment. A debriefing outline with teaching points is provided. In some cases, students may stray from the case, either following alternative diagnoses or ordering unnecessary, time-consuming tests. Although allowing some autonomy to proceed with care may be instructive, the instructor must balance autonomy with the desired teaching points of the case. A second section of the case covering management after disposition from the emergency department may be added. This provides teaching points from initial presentation to discharge from the hospital, combining many aspects often not seen or treated by the same practitioner.